Determinants of breastfeeding initiation among mothers in Sydney, Australia: findings from a birth cohort study - Arora, A.; Manohar, N.; Hayen, A.; Bhole, S.; Eastwood, J.; Levy, S.; Scott, Jane (BioMed Central, 2017)
Background: Breastfeeding has short-term and long-term benefits for both the infant and the mother. The objective of this study was to identify the incidence of breastfeeding initiation among women in South Western Sydney, and the factors associated with the initiation of breastfeeding. Methods: Child and Family Health Nurses recruited mother-infant dyads (n = 1035) to the Healthy Smiles Healthy Kids birth study in South Western Sydney, an ethnically and socio-economically diverse area, at the first post-natal home visit. A sample of 935 women completed a structured, interviewer-administered questionnaire at 8 weeks. Multivariate logistic regression analysis was used to identify those factors independently associated with the initiation of breastfeeding. Results: In total, 92% of women (n = 860) commenced breastfeeding in hospital. Women who completed a university degree were more likely to initiate breastfeeding compared to those who did not complete high school (AOR = 7.16, 95% CI 2.73, 18.79). Vietnamese women had lower odds of breastfeeding initiation compared to Australian born women (AOR = 0.34. 95% CI 0.13, 0.87). Women who had more than one child were less likely to breastfeed than those who had one child (AOR = 0.38, 95% CI 0.19, 0.79). Women who gave birth via a caesarean section were less likely to breastfeed their baby compared to those who had a vaginal delivery (AOR = 0.27, 95% CI 0.14, 0.52). Women who drank alcohol during pregnancy had 72% lower odds to breastfeed compared to those who did not drink alcohol during pregnancy (AOR = 0.28, 95% CI 0.11, 0.71). Women who reported that their partner preferred breastfeeding were more likely to initiate breastfeeding (AOR = 11.77, 95% CI 5.73, 24.15) and women who had chosen to breastfeed before pregnancy had more than 2.5 times the odds of breastfeeding their baby compared to those women who made their decision either during pregnancy or after labour (AOR = 2.80, 95% CI 1.31, 5.97). Conclusions: Women with lower levels of education, who consume alcohol during pregnancy, have more than one child, and make infant feeding decision after becoming pregnant, and those born in Vietnam should be targeted when implementing breastfeeding promotion programs. Further, women who deliver by caesarean section require additional breastfeeding support post-delivery and it is important to include fathers in breastfeeding related decisions and encourage them to participate in antenatal programs.